Зимовий бал Тетяни Клименко - Мельник, Г.О. (Архіви України, 2010)
Висвітлено трудовий шлях директора Державного архіву Черкаської області Тетяни Анатоліївни Клименко, яка понад двадцять років працює в архіві. Освещён трудовой путь директора Государственного архива Черкасской области Татьяны Анатольевны Клименко, которая более двадцати лет своей жизни посвятила архивному делу. The article was written on the occasion of fiftieth birthday of the director of The State Archives of Cherkassy region Klymenko Tetyana, whose twenty years seniority is connected with Cherkassy Archives.